2018
DOI: 10.3390/ijerph15040660
|View full text |Cite
|
Sign up to set email alerts
|

Improving Chronic Disease Self-Management by Older Home Health Patients through Community Health Coaching

Abstract: The purpose of the study was to pilot test a model to reduce hospital readmissions and emergency department use of rural, older adults with chronic diseases discharged from home health services (HHS) through the use of volunteers. The study’s priority population consistently experiences poorer health outcomes than their urban counterparts due in part to lower socioeconomic status, reduced access to health services, and incidence of chronic diseases. When they are hospitalized for complications due to poorly ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 32 publications
0
30
0
1
Order By: Relevance
“…Thus, patients should be equipped with the right skillsets for self-care. Various studies identified the need to facilitate self-management and provide adequate support, for example, through community programmes [59][60][61][62][63][64][65][66]. Although healthcare providers might have provided self-management guidelines and support to polyclinic patients, our study found that patients' practices were still affected by their daily activities involving work and the community, as well as their beliefs and physical condition.…”
Section: Key Findings and Recommendationsmentioning
confidence: 66%
“…Thus, patients should be equipped with the right skillsets for self-care. Various studies identified the need to facilitate self-management and provide adequate support, for example, through community programmes [59][60][61][62][63][64][65][66]. Although healthcare providers might have provided self-management guidelines and support to polyclinic patients, our study found that patients' practices were still affected by their daily activities involving work and the community, as well as their beliefs and physical condition.…”
Section: Key Findings and Recommendationsmentioning
confidence: 66%
“…As such, patients should be equipped with the right skillset for self-care. Various studies identified the need to facilitate self-management and provide adequate support, for example through community programmes (55)(56)(57)(58)(59)(60)(61)(62). Even though healthcare providers might have provided self-management guidelines to polyclinic patients, our study found that patients' practices were also affected by their daily activities involving work and the community, as well as their beliefs and physical condition.…”
Section: Key Findings and Recommendationsmentioning
confidence: 66%
“…Thus, patients should be equipped with the right skillsets for self-care. Various studies identified the need to facilitate self-management and provide adequate support, for example, through community programmes (59)(60)(61)(62)(63)(64)(65)(66). Although healthcare providers might have provided selfmanagement guidelines and support to polyclinic patients, our study found that patients' practices were still affected by their daily activities involving work and the community, as well as their beliefs and physical condition.…”
Section: Key Findings and Recommendationsmentioning
confidence: 66%